2022
DOI: 10.3389/fpsyg.2022.935822
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Significance of Motivation on Job Satisfaction and Performance Among the Academicians: The Use of Hybrid Structural Equation Modeling-Artificial Neural Network Analysis

Abstract: The competition in higher education has increased, while lecturers are involved in multiple assignments that include teaching, research and publication, consultancy, and community services. The demanding nature of academia leads to excessive work load and stress among academicians in higher education. Notably, offering the right motivational mix could lead to job satisfaction and performance. The current study aims to demonstrate the effects of extrinsic and intrinsic motivational factors influencing job satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Practicing medical care during a pandemic is a challenge for nurses (Tyer-Viola, 2019) and can result in higher occupational stress and low job satisfaction (Kwiecień-Jaguś et al, 2018;Leskovic et al, 2020). Conversely, medical professionals with a higher degree of fit have higher job satisfaction (Sinniah et al, 2022). The moderating role of optimism…”
Section: The Mediating Role Of Perceived Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Practicing medical care during a pandemic is a challenge for nurses (Tyer-Viola, 2019) and can result in higher occupational stress and low job satisfaction (Kwiecień-Jaguś et al, 2018;Leskovic et al, 2020). Conversely, medical professionals with a higher degree of fit have higher job satisfaction (Sinniah et al, 2022). The moderating role of optimism…”
Section: The Mediating Role Of Perceived Stressmentioning
confidence: 99%
“…Although public attention has focused primarily on the relationship between grit and achievement, grit has also been highlighted as a predictor of nurses’ subjective well-being ( Seguin, 2019 ). Positive personality traits are motivation to promote job satisfaction ( Sinniah et al, 2022 ), and grit as a personality strength affects people’s subjective well-being and is a significant predictor of job satisfaction in particular ( Goodman et al, 2017 ). A meta-analysis ( Hou et al, 2022 ) has shown that grit was positively associated with job satisfaction, suggesting that more extraordinary grit was associated with greater job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…In order to find the relationship between the culture of a HEI and teachers' job satisfaction, a conducted literature review (Abid Alvi, et al, 2014;Bahir, 2020;Pavlović, et al, 2020;Serinkan & Kiziloglu, 2021;Blömeke, et al, 2021;Smith, 2021;Sinniah, et al 2022;Chonody, et al 2022;Sell, 2023;Borrego, et al 2023;Geiger, et al 2023;Chen, 2023, etc.) revealed more detailed findings of the factors of HEI culture that affect teachers' job satisfaction (Table 1). Sell (2023) argues that maintaining transparency in decision-making and resource allocation is important in creating workplaces that support employee well-being.…”
Section: Theoretical Justification Of the Impact Of The Culture Of A ...mentioning
confidence: 99%
“…Personal factors such as professional development and career progression are also addressed in the context of the impact of the culture of a HEI on teachers' job satisfaction. According to Yang & Hwang (2014), Sinniah et al (2022), Borrego, et al (2023), professional development opportunities empower teachers of a HEI psychologically, boost their intrinsic motivation and increase job satisfaction. According to Sell (2023) and Chen (2023), in order to ensure employee job satisfaction, it is important for institutions to provide a better work-life balance and to expand professional development opportunities.…”
Section: Theoretical Justification Of the Impact Of The Culture Of A ...mentioning
confidence: 99%
See 1 more Smart Citation